Periadnexal Mucin as an Additional Histopathologic Feature of Chronic Eczematous Dermatitis - Lee, Noo Ri (Ann Dermatol, 2015)
BACKGROUND: Cutaneous mucinoses are a heterogeneous group of disorders characterized by an abnormal amount of mucin in the skin. However, the pathomechanism of an excessive mucin deposition in the skin is still unknown. Eczematous dermatitis is sub-classified histologically into acute, subacute, and chronic variants. The characteristic histopathologic findings for chronic eczema are variable. However, periadnexal mucin deposition is not known as a feature of chronic eczema. OBJECTIVE: To evaluate the presence of periadnexal mucin deposition in chronic eczematous dermatitis. METHODS: We analyzed the skin biopsy specimens from 36 patients who were pathologically diagnosed with chronic eczematous dermatitis. Alcian blue, colloidal iron, and periodic acid-Schiff stains were used to evaluate the mucin deposition in histologic sections. Two dermatologists and two dermatopathologists evaluated the degree of mucin deposition using a 4-point scale. RESULTS: Various amounts of mucin deposition were observed in the periadnexal area of patients who were diagnosed with chronic eczema. Mucin deposition was more visible after staining with mucin-specific stains. Evaluation of the staining analysis scores revealed that the staining intensities were significantly higher in patients with chronic eczema than age- and site-matched controls (normal, acute to subacute eczema, and psoriasis vulgaris). CONCLUSION: Periadnexal mucin (secondary mucinoses) may be an additional finding of chronic eczematous dermatitis.